Associations between anxiety, depression, and sleep problems in women during the COVID-19 pandemic: a cross sectional study - Çatalgöl, Şeyma; Akgün, Rabia (The European Research Journal, 2025)
Objectives: This study was conducted to determine the association between anxiety, depression, and sleep problems in women during the COVID-19 pandemic. Methods: This cross-sectional study included 686 women via a web survey between February 20, 2021, and April 9, 2021. In this study, participants' anxiety scores were evaluated with the Beck Anxiety Inventory (BAI), depression findings with the Beck Depression Inventory (BDI), and sleep quality scores with the Pittsburgh Sleep Quality Index (PSQI). Cut-off points: PSQI >5 indicates poor sleep quality, BAI 16-25 indicates moderate, and ≥26 indicates severe anxiety; BDI 17-29 indicates moderate, and ≥30 indicates severe depression. Statistical analyses included t-test, ANOVA, Pearson correlation, and multiple linear regression. Results: The younger age group, students, singles, smokers, and alcohol users were at higher risk for increased anxiety, depression, and poor sleep quality during the COVID-19 pandemic. Participants exhibited high levels of anxiety (moderate anxiety in 20.12%, severe anxiety in 20.70%), depression (moderate depression in 25.22%, severe depression in 12.53%), and poor sleep quality (58.6%). A moderate positive correlation was found between sleep quality and anxiety (r=0.517, P